Lihdumneeks: the use of antiqua typefaces in a pioneering Latvian newspaper printed in Brazil - Piaia, Jade Samara; Farias, Priscila Lena; Straumanis, Andris (Baltistica, 2021)
This article analyses a pioneering Latvian newspaper published in São Paulo between 1907 and 1909. The focus of the analysis are the typefaces and the adaptations needed for printing Latvian using antiqua1 rather than blackletter type2, most commonly used in Latvia in that period. The adaptations made demonstrate the effort of the editor Jūlijs Malvess and the Brazilian printers of German descent, Hennies Irmãos (Hennies Brothers), to make the contents of the newspaper understandable for immigrants newly settled in Latvian colonies in São Paulo state. The typefaces used by the Brazilian printers in this publication were identified, revealing what seems to be a modern typographic taste that did not privilege the use of blackletter typefaces.